PERLINDUNGAN HUKUM BAGI SATUAN GEGANA BRIMOB POLRI DALAM PENANGANAN KEJAHATAN BERBASIS SENJATA API DAN BAHAN PELEDAK (Studi Kasus Polda Sumatera Utara) - Mikhael Sinaga (YAPEKAM, 2025)
The Gegana Unit of the Mobile Brigade (Brimob) of the Indonesian National Police is a special force that plays a strategic role in handling high-risk crimes, such as the use of firearms and explosives that threaten national security. The complexity and dangers inherent in these tasks demand clear and effective legal protection for each personnel involved. However, in practice, the existing legal protections are often not optimally implemented, potentially creating legal dilemmas in the field. This study aims to analyze the legal regulations governing the protection of the Gegana Unit, identify obstacles in their implementation, and formulate efforts to strengthen legal protection for Gegana personnel in the performance of their duties. The research uses a juridical-empirical method with a qualitative approach. Data were collected through interviews with Gegana Brimob officers in North Sumatra Regional Police, literature studies on relevant regulations, and direct observation of operational practices. The results show that legal protections are normatively provided under various regulations, such as Law No. 2 of 2002 and Emergency Law No. 12 of 1951. However, implementation still faces obstacles such as lack of legal understanding among personnel, non-adaptive standard operating procedures (SOPs), and public and media pressure. Improvement efforts have been made through legal training, SOP revisions, legal assistance, and operational documentation digitalization. This study recommends strengthening inter- institutional synergy and preventive legal education to ensure more effective and comprehensive legal protection for the Gegana Unit.